2015
DOI: 10.1080/16089677.2015.1056478
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and association of low testosterone levels in a South African male, diabetic, urban population

Abstract: Background: According to the literature, low serum testosterone levels are associated with diabetes mellitus. No or minimal data exist for its prevalence or predictors in South Africa. Design: This was a cross-sectional study. Setting: The setting was an academic centre, i.e. the University of Pretoria and Steve Biko Academic Hospital Diabetes Clinic. Subjects: A total of 150 consecutive male patients aged 50 years and older with diabetes mellitus were selected using convenience sampling. Outcome measures: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
1
8
3
Order By: Relevance
“…This variable also did not correlate with TT in similar studies conducted in South Africa and New York. 16,17 In contrast to this study, a study conducted in Jordan reported a significant positive correlation of age with TT. 25 Studies in England and Nigeria reported the presence of a significant negative correlation between age and TT level.…”
Section: Correlation Of Serum Total Testosterone Level With Independecontrasting
confidence: 98%
See 1 more Smart Citation
“…This variable also did not correlate with TT in similar studies conducted in South Africa and New York. 16,17 In contrast to this study, a study conducted in Jordan reported a significant positive correlation of age with TT. 25 Studies in England and Nigeria reported the presence of a significant negative correlation between age and TT level.…”
Section: Correlation Of Serum Total Testosterone Level With Independecontrasting
confidence: 98%
“…The prevalence of hypogonadism in this study was lower than that of similar studies conducted in different countries 11,[16][17][18][19][20][21][22] but a study conducted in Iran reported a lower prevalence. 23 Possible explanations for these variations in the prevalence of hypogonadism in this population group may be a variation in the type of testosterone measured, whether TT or free testosterone, the cut-off value of TT or free testosterone, age categories of the study subjects, the prevalence of obesity, diabetic duration, study design and laboratory methods used.…”
Section: Prevalence Of Hypogonadism Among the Study Subjectscontrasting
confidence: 90%
“…9 Although it was originally developed in a non-diabetic Caucasian population, the ADAM questionnaire is widely used in Africans and diabetics despite absence of evidence of its reliability in this population. 12,13 This study was aimed at evaluating the accuracy of the ADAM questionnaire as a tool for clinical detection of AD in sub-Saharan African men with type 2 DM.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Onung et al and Ugwu et al reported the prevalence of hypogonadism to be 38.9% and 52.5% in men with T2DM in Lagos and Ile-Ife, respectively [15][16][17]. In South Africa, Kemp et al reported the prevalence of androgen deficiency symptoms to be 94.7% among male diabetics aged 50 years and above [18]. The mechanisms underpinning hypogonadism in T2DM have been postulated to include obesity, adipocytokine mediated inhibition of gonadotropins and leydig cell dysfunction, testicular steroidogenesis inhibition, hyperoestrogenaemia due to exaggerated aromatase activity and decreased sex hormone-binding globulin levels [7,10,13,19].…”
Section: Introductionmentioning
confidence: 99%